2011
DOI: 10.1016/j.stem.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Crosstalk between Bmi1 and MLL/Hoxa9 Axis in Establishment of Normal Hematopoietic and Leukemic Stem Cells

Abstract: Bmi1 is required for efficient self-renewal of hematopoietic stem cells (HSCs) and leukemic stem cells (LSCs). In this study, we investigated whether leukemia-associated fusion proteins, which differ in their ability to activate Hox expression, could initiate leukemia in the absence of Bmi1. AML1-ETO and PLZF-RARα, which do not activate Hox, triggered senescence in Bmi1(-/-) cells. In contrast, MLL-AF9, which drives expression of Hoxa7 and Hoxa9, readily transformed Bmi1(-/-) cells. MLL-AF9 could not initiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 56 publications
(72 reference statements)
5
99
1
Order By: Relevance
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 55%
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 55%
“…Especially, expression of Bmi1, which is required for self-renewal in HSCs and leukemic stem cells is elevated in GMPs. 32 Of importance in regard to chemotherapy resistance of AML is also the upregulated expression of Mcl1 in GMPs of Cebpa K/L x Flt3 ITD/ þ chimeras. Expression of the pro-survival gene Mcl1, a member of the BCL2 family and a crucial regulator of HSC survival, has been implicated in the pathogenesis of AML.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous null Pcgf4/Bmi1 mouse mutant phenotypes are attributed mainly to the depletion of the classical cPRC1 complexes (Table 4). Pcgf4/Bmi1 functions required for postnatal stem cell maintenance of multiple tissues including hematopoietic [306,307] and neural [308,309]. Pcgf4/Bmi1 null mutant mice are viable but display progressive postnatal growth retardation, defect in hematopoiesis and neurological abnormalities manifested by seizures [148].…”
Section: Ncprc12 and Ncprc14mentioning
confidence: 99%
“…Genome-wide studies suggested that PRC1.5 complexes encompassing CK2 and AUTS2 are recruited to active genes, uncovering a new function of the PRC1.5 in activating transcription ( [313] and see below). [148,306,307,310] CK2 belongs to the serine/threonine-selective protein kinase family. CK2 is consisted of two α (α and α') and two β (β and β') subunits, foremost of which α is responsible for the catalytic and β for the regulatory activity.…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 99%